Formação continuada: reflexão sobre as contribuições da tecnologia para o desenvolvimento profissional docente - Maia, Fernanda Jardim [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The scope of this work is directly related to the Covid-19 pandemic and the consequences of social distancing on the implementation of digital resources in education. As the world struggled to survive the unexpected challenges imposed by safety measures to contain the virus, education had to learn, recycle, and reinvent itself to bridge the gap between teachers, students, and knowledge. The problem of this research originated from the question of how teachers without technological training could instantly adapt to be able to seek and use digital resources as a learning situation proposal and how this can be an opportunity to propose necessary changes and train professionals prepared for the new reality of education. This is an applied research with an exploratory and qualitative approach. It uses the conceptions of Tardif (2014), Marcelo (1999, 2001, 2022), Imbernón (2009, 2010, 2024), Veiga (2007, 2008), Kenski (2012), Moran (2001, 2004, 2015, 2019), among others, as its foundation. For data collection, questionnaires were used with 69 tenured teachers, semi-structured interviews with 7 teachers and 10 managers of a municipal education network in a city in the interior of São Paulo, in addition to documentary analysis of the Political Pedagogical Projects of the schools participating in the research. The analysis was carried out through the methodological proposal of Meaning Cores, based on socio-historical psychology, mainly grounded in Vygotsky (1991; 2000). The results show that although teachers recognize the importance of continuing education for the use of technology in education, their understanding of the effective integration of Digital Information and Communication Technologies (DICTs) into pedagogical practice is still superficial, often limited to using technologies as accessory tools rather than didactic-pedagogical elements. The analysis of the training offered by the REM revealed a disconnection between theory and practice, hindering the implementation of active methodologies and the optimized use of available technological resources. It was also found that the excessive bureaucratic load and the lack of proficiency with DICTs, among many teachers and managers, as well as the students themselves, represent barriers to pedagogical innovation. The analysis of the meaning cores "The role of technology for and in teacher professional qualification," "Challenges of teaching in current scenarios," and "Processes and setbacks in human and professional teacher development" deepened the understanding of the difficulties faced by teachers and the possibilities for intervention in continuing education for effective integration of technology into pedagogical practice.

O escopo deste trabalho está diretamente relacionado ao momento Pandemia Covid-19 e as consequências do afastamento social para implementação dos recursos digitais na educação. Quando o mundo lutava para sobreviver aos desafios inesperados impostos pelas medidas de segurança para conter o vírus, a educação precisou aprender, reciclar e se reinventar, para transpor a distância entre professores, alunos e conhecimento. O problema desta pesquisa originou-se pelo questionamento sobre como professores sem formação tecnológica poderiam adequar-se instantaneamente para serem capazes de buscar e utilizar recursos digitais como proposta de situação de aprendizagem e como esta pode ser uma oportunidade para propor alterações necessárias e formar profissionais preparados para a nova realidade da educação. Trata-se de uma pesquisa aplicada, de cunho exploratório e abordagem qualitativa. Para tanto, utiliza-se como fundamento as concepções de Tardif (2014), Marcelo (1999, 2001, 2022), Imbernón (2009, 2010, 2024), Veiga (2007, 2008), Kenski (2012) Moran (2001, 2004, 2015, 2019), entre outros. Para a coleta das informações foi utilizado como instrumento de coleta: questionários com 69 professores efetivos, entrevistas semiestruturadas com 7 professores e 10 gestores de uma rede municipal de ensino de uma cidade do interior de São Paulo, além de análise documental dos Projetos Políticos Pedagógicos das escolas participantes da pesquisa. A análise foi realizada por meio da proposta metodológica de Núcleos de significação, com base na psicologia sócio-histórica, fundamentada sobretudo em Vygotsky (1991; 2000). Os resultados evidenciam que, embora os docentes reconheçam a importância da formação continuada para o uso da tecnologia na educação, sua compreensão sobre a integração efetiva das Tecnologias de Digitais de Informação e Comunicação (TDICs) à prática pedagógica ainda é superficial, frequentemente limitada à utilização das tecnologias como ferramentas acessórias, em vez de elementos didático-pedagógicos. A análise das formações ofertadas pela REM revelou uma dissociação entre a teoria e a prática, dificultando a implementação de metodologias ativas e o uso otimizado dos recursos tecnológicos disponíveis. Constatou-se, ainda, que a excessiva carga burocrática e a falta de proficiência com as TDICs, de muitos professores e gestores, e dos próprios alunos, representam barreiras para a inovação pedagógica. A análise dos núcleos de significação "O papel da tecnologia para e na qualificação profissional docente", "Desafios da docência nos cenários atuais" e "Processos e retrocessos do desenvolvimento humano e profissional docente" aprofundou a compreensão sobre as dificuldades enfrentadas pelos docentes e as possibilidades de intervenção na formação continuada para uma efetiva integração da tecnologia à prática pedagógica.
Continuing education: reflection on the contributions of technology to teacher professional development
Keywords: Educação tecnológica; Propostas políticas; Formação docente continuada; Technological education; Political proposals; Continuous teacher training